Money for business : A guide prepared by the Bank of England and the city communications centre - Bank of England (England : Stephen Austin and sons Limited, Hertford, 1980)
This is in no sense a manual of financial management, and it is not intended as a substitute for finding a good financial adviser. The guide offers a general description, for those who are not themselves experienced in the technicalities of raising funds for business, of how to assess their need for new money, and of the characteristics and appropriateness of particular kinds of finance.
New impression with minor corrections January 1979
Includes bibliographical references
hza 17/09/2018
Loans
Keywords: Investment banking